Every‐other‐day palonosetron plus aprepitant for prevention of emesis following induction chemotherapy for acute myeloid leukemia: A randomized, controlled study from the "Rete Ematologica Pugliese". (14th November 2019) - Di Renzo, Nicola; Melillo, Lorella; Porretto, Fernando; Dargenio, Michela; Pavone, Vincenzo; Pastore, Domenico; Mazza, Patrizio; Mannina, Donato; Merenda, Anxur; Cascavilla, Nicola; Greco, Giuseppina; Matera, Rosella; et al.
Abstract: Background: Compared with older 5‐HT3 receptor antagonists, palonosetron requires fewer drug administrations to prevent chemotherapy‐induced nausea and vomiting (CINV) following multiple‐day chemotherapy. We conducted a phase II multicenter study comparing palonosetron plus aprepitant to palonosetron alone in patients undergoing a range of induction chemotherapy regimens for acute myeloid leukemia (AML). Methods: Patients were randomized to palonosetron (0.25 mg) every other day until the last dose of chemotherapy alone or with aprepitant on days 1‐3. Patients mainly received an anthracycline on days 1‐3 plus cytarabine administered for 5‐10 days. The primary end point was complete response (CR; no emesis and no rescue medication) over the whole study period (days of chemotherapy plus two additional days). Unplanned analysis of time to anti‐emetic treatment failure (TTF) was also performed. Results: Of the 134 patients enrolled in the study, 130 were evaluable: 68 subjects received palonosetron plus aprepitant and 62 received palonosetron alone. Although the primary end point of CR was similar between the treatment arms (72% vs 69%; P  = .55), a higher proportion of patients treated with palonosetron plus aprepitant were free from nausea during the whole study period (43% vs 27%; P  = .03). There was also a significant difference in favor of the two‐drug regimens in TTF (median: 5 days vs 3 days; P  = .03). Conclusions: The study suggests that every‐other‐day palonosetron plus 3‐day aprepitant can add clinical benefit to the control of CINV caused by multiple‐day, corticosteroid‐free chemotherapy for AML. In this challenging setting of CINV, further investigations of palonosetron in combination with aprepitant administered with an expanded schedule are warranted. ClinicalTrial.gov identifier: NCT02205164. Abstract : In this randomized study on acute myeloid leukemia patients treated with multiple‐day induction chemotherapy, the authors investigated the efficacy of a simplified antiemetic prophylaxis consisting of every‐other‐day palonosetron plus 3‐day aprepitant compared to palonosetron alone. Although similar rates of complete response were observed, the combination regimen significantly improved control of nausea in this challenging setting of chemotherapy‐induced nausea and vomiting.